PENGARUH OLI FULL-SYNTHETIC VS SEMI-SYNTHETIC TERHADAP PERFORMA SEPEDA MOTOR 4 TAK 250 CC - Zapit, Dandi Wahyudi; Sugiarto, Toto; Wagino, Wagino; Fernandez, Donny (Ensiklopedia Research and Community Service Review, 2025)
Abstract: The right oil selection is critical in maintaining the performance of a motorcycle engine, given its role in lubrication, cooling, and reducing friction between components. This study aims to analyze the effect of semi-synthetic and full-synthetic oils on oil temperature, engine vibration, torque, and power on 4 Stroke 250 CC motorcycles to provide comprehensive information to motorcycle users about the types of oils that can optimize engine performance. The research method uses an experimental approach with a Kawasaki Ninja 250 RR Mono motorcycle as the object of study. The test was carried out at various engine revolutions (RPM) by measuring vibration using a vibration meter, temperature with a thermocouple, and torque and power through a dyno test. Data analysis uses descriptive statistics to determine significant differences between oils. The study results show that full-synthetic oil consistently provides more optimal engine performance than semi-synthetic oil. Full-synthetic produces lower vibration, maintains stable temperatures, and produces higher torque and power at each RPM. These findings indicate that full-synthetic oils can improve engine efficiency, reduce the risk of damage, and extend the life of motorcycles.Keywords: Semi-synthetic Oil, Full-synthetic Oil, Engine Vibration, Oil Temperature, Engine Performance.